Diametrical growth in the forward flow forming process: Simulation, validation, and prediction - Song, X; Fong, K; Oon, SR; Tiong, W; Li, P; Korsunsky, A; Danno, A (2014)
In the present study, the phenomenon of diametric growth in the forward flow forming process has been studied through finite element simulation and experimental investigation. Implicit integration scheme was employed in the simulation to achieve good accuracy for diametric growth prediction. The simulation results were in good agreement with the experiments for both types of materials considered, the aluminum alloy AA6061 and stainless steel SS304L. The residual stresses in the flow-formed parts were measured using x-ray diffraction to validate the model as well as provide the explanation for the diametric growth behavior. Based on the numerical and experimental results, an empirical function was proposed here to describe the amount of diametric growth in the flow-formed parts, which can be used as a predictive tool for dimension control in the flow forming process. © 2013 Springer-Verlag London.